Exploring the atmospheric and ecological impacts of a major dust storm: Insights from WRF–Chem simulations - Yang, Hongwei; Fu, Wenxuan (Aeolian research, 2025)
•A severe dust event was simulated by the WRF–Chem model.•Dust aerosols generally had a negative impact on GPP.•Dust aerosols reduced GPP exceeding 10% in some areas.•Changes in GPP were caused by interactions among various factors. Sand and dust storm (SDS) is disastrous weather phenomenon on a global scale. Previous studies have demonstrated that SDS significantly affects weather, air quality, and human health. However, the interaction between SDS and ecological systems has previously been underexplored. In this study, we aim to elucidate the impact mechanisms of SDS on vegetation dynamics. We employed Weather Research and Forecast (WRF) model with Chemistry (WRF–Chem) to investigate the severe SDS in East Asia in May 2017. Our results reveal that the WRF–Chem model reasonably reproduced the large scale eastward movement of the SDS caused by the Mongolia cyclone in multiple aspects. SDS decreased downward shortwave (SW) radiation at surface (DSWS) and increased longwave radiation at the surface, causing non-uniform spatiotemporal changes in skin temperature (SKT) determined by the local surface energy balance. Crucially, SDS detrimentally impacted gross primary production (GPP) during the critical germination phases, with reductions in GPP exceeding 10% in certain areas. The total reductions were −20.17 kt, −81.55 kt, and −218.88 kt, respectively for May 2, 3, and 4 over the domain. Changes in GPP were attributed to variations in SKT and DSWS, as determined by calculating the partial correlation coefficients (PCC). The sensitivity, magnitude, and direction of GPP variation due to SKT and DSWS were influenced by altitude, which inherently affects radiation levels. These variations were further modulated by local conditions, including moisture availability. Our study illuminates the interaction between SDS and ecological systems, a subject that has been poorly understood.